Istota i geneza zasady ostrożnej wyceny - Hońko, Stanisław (Substance and Genesis of Prudence Principle, 2005)
This article outlines the substance and range of prudence principle in accountancy. The genesis and stages of development since 17th century was also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 85-94